TEACHERS' EFFORTS TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS AT AL-IKHWAN IT JUNIOR HIGH SCHOOL - Setiawan, Erik; Fitri Silvia Sofyan; Lusiana Rahmatiani (Journal Civics And Social Studies, 2024)
Critical thinking is one of the key skills that need to be developed in 21st century education. Critical thinking not only helps students in understanding subject matter more deeply, but also equips them with the ability to analyze information, evaluate arguments, and solve problems effectively. The ability to think critically is needed in social life, therefore students must familiarize it from an early age, then develop it through education in schools. The development of critical thinking skills must be accompanied by the formation of better skills and attitudes. The purpose of this study was to determine the teacher's efforts to improve the critical thinking skills of students at Al-Ikhwan IT Junior High School. The method used is descriptive method often called naturalistic research method because it is done in natural conditions (natural setting). This method is based on the philosophy of postpositivism and is used to examine objects in natural conditions, where researchers act as key instruments. Data collection is done in triangulation (combined), data analysis is qualitative inductive, and research results emphasize meaning rather than generalization. This study collects information by using interview data to the principal and Civics teacher at Al-ikhwan IT Junior High School The results of this study are that the teacher has tried to improve the quality of the students' learning. Keywords: Teacher, Critical Thinking